2014
DOI: 10.24199/j.mmv.2014.71.19
|View full text |Cite
|
Sign up to set email alerts
|

Systematics, evolution and phylogeny of Annelida – a morphological perspective

Abstract: Purschke, G., Bleidorn, C. and Struck, T. 2014. Systematics, evolution and phylogeny of Annelida -a morphological perspective . Memoirs of Museum Victoria 71: 247-269.Annelida, traditionally divided into Polychaeta and Clitellata, is an evolutionary ancient and ecologically important group today usually considered to be monophyletic. However, there is a long debate regarding the in-group relationships as well as the direction of evolutionary changes within the group. This debate is correlated to the extraordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 108 publications
3
46
0
Order By: Relevance
“…Likewise, the epidermis and cuticle are always thinner than in other parts of the body. It should be noted that the annelid cuticle is a soft and flexible, rather than tight, border and is typically traversed by numerous microvilli (Hausen, 2005;Purschke et al, 2014). Mostly, annelid branchiae are supplied with efferent and afferent vessels, which give rise to some kind of connecting vessel and often blind-ended blood spaces extending deeply into the epidermal cells.…”
Section: Discussion the Branchiaementioning
confidence: 99%
“…Likewise, the epidermis and cuticle are always thinner than in other parts of the body. It should be noted that the annelid cuticle is a soft and flexible, rather than tight, border and is typically traversed by numerous microvilli (Hausen, 2005;Purschke et al, 2014). Mostly, annelid branchiae are supplied with efferent and afferent vessels, which give rise to some kind of connecting vessel and often blind-ended blood spaces extending deeply into the epidermal cells.…”
Section: Discussion the Branchiaementioning
confidence: 99%
“…In addition, these are usually found in highly derived positions in the phylogenetic tree. Yet, such a body plan of ground-dwelling annelids is now found to be highly derived [22] and the subepidermal position of their ventral nerve cord may either be a protective adaptation to the mechanic stress during burrowing or related to the necessity of a well-developed system of circular muscle fibers. Notably, in species with an intraepidermal VNC, the ventral longitudinal muscle bundles are usually separated from each other by the VNC and true circular musculature forming closed rings of fibers is absent [86,87].…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…Nonetheless, the annelid VNC shows a great diversity in number and position of neurite bundles and localization either within or beneath the epidermis [1,4,5,7,20,21]. Accordingly, the hypothesis that the ladder-like VNC is ancestral was often questioned [21][22][23][24] and challenged repeatedly, e.g., by a hypothesis regarding a pentaneuralian arrangement of the neurite bundles in the annelid VNC as ancestral [4, 5; rejected in 25] and by the finding of an unpaired mid-ventral nerve cord in numerous taxa [15,21,24,[26][27][28]. Recent, well-supported phylogenomic analyses [29][30][31][32][33] revealed that previous profound investigations into annelid neuroanatomy unfortunately focussed on representatives of derived annelid subgroups, now united as Pleistoannelida [4,5,21].…”
Section: Introductionmentioning
confidence: 99%
“…Annelids (bristle worms, earthworms, and leeches) are a spiralian taxon with segmented body plans and a predominant VNC with variable composition (Hejnol & Lowe, ; Müller, ; Purschke, Bleidorn, & Struck, ). Within Annelida, the ancestral nervous system was historically inferred to include a rope‐ladder‐like ventral cord (Bullock & Horridge, ; Orrhage & Müller, ; Purschke, ), with bilateral pairs of iterated ganglia joined by longitudinal connectives and transverse commissures (Richter et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Within Annelida, the ancestral nervous system was historically inferred to include a rope‐ladder‐like ventral cord (Bullock & Horridge, ; Orrhage & Müller, ; Purschke, ), with bilateral pairs of iterated ganglia joined by longitudinal connectives and transverse commissures (Richter et al, ). However, recent work has highlighted a diversity of neural arrangements among adult annelids, including species in some taxa with medullary cords and others with ventral cords containing intraepidermal neurons (Helm et al, ; Purschke, ; Purschke et al, ). And within the last decade, a series of phylogenomic studies (Andrade et al, ; Helm et al, ; Struck et al, , ; Weigert et al, ; Weigert & Bleidorn, ) have produced new hypotheses for alternative clade arrangements, followed by subsequent ancestral character state reconstructions of annelid VNC architecture suggesting that rope‐ladder‐like arrangements may have evolved more than once, through convergence (Helm et al, ).…”
Section: Introductionmentioning
confidence: 99%